PENENTUAN PARAMETER-PARAMETER KARAKTERISTIK SEL SURYA UNTUK KONDISI GELAP DAN KONDISI PENYINARAN DARI KURVA KARAKTERISTIK ARUS-TEGANGAN (I-V) - Suhandi, A.; Tayubi, Y. R.; Hikmat, Hikmat; Eliyana, A. (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2008)
A systematic procedure to obtain the main parameters which characterize a commercial solar cells, both in dark conditions (series and shunt resistances and recombination and diffusion saturation currents) and also under illumination (short circuit current, open circuit voltage and fill factor) are presented in this paper. All the measurements needed are made with simple and inexpensive apparatus and the calculations are straightforward.